A modular microarray imaging system for highly specific COVID-19 antibody testing. Issue 18 (3rd August 2020) - Hedde, Per Niklas; Abram, Timothy J.; Jain, Aarti; Nakajima, Rie; Ramiro de Assis, Rafael; Pearce, Trevor; Jasinskas, Algis; Toosky, Melody N.; Khan, Saahir; Felgner, Philip L.; Gratton, Enrico; Zhao, Weian
Abstract : The TinyArray imager, a robust inexpensive portable imaging device, can detect antibodies against SARS-CoV-2 based on coronavirus antigen microarrays. Abstract : To detect the presence of antibodies in blood against SARS-CoV-2 in a highly sensitive and specific manner, here we describe a robust, inexpensive ($200), 3D-printable portable imaging platform (TinyArray imager) that can be deployed immediately in areas with minimal infrastructure to read coronavirus antigen microarrays (CoVAMs) that contain a panel of antigens from SARS-CoV-2, SARS-1, MERS, and other respiratory viruses. Application includes basic laboratories and makeshift field clinics where a few drops of blood from a finger prick could be rapidly tested in parallel for the presence of antibodies to SARS-CoV-2 with a test turnaround time of only 2–4 h. To evaluate our imaging device, we probed and imaged coronavirus microarrays with COVID-19-positive and negative sera and achieved a performance on par with a commercial microarray reader 100× more expensive than our imaging device. This work will enable large scale serosurveillance, which can play an important role in the months and years to come to implement efficient containment and mitigation measures, as well as help develop therapeutics and vaccines to treat and prevent the spread of COVID-19.